2015
DOI: 10.3390/su7044120
|View full text |Cite
|
Sign up to set email alerts
|

Social Values and Sustainability: A Survey on Drivers, Barriers and Benefits of SA8000 Certification in Italian Firms

Abstract: Abstract:Companies are increasingly required to deal with sustainability issues through the adoption of Corporate Social Responsibility (CSR) practices. Among the different CSR aspects, workers securities fulfill a necessary issue. SA8000 is an internationally accepted tool that aims to guarantee decent workplace across all industrial sectors. Italian companies represent more than 30% of certified organizations on a global level. Company size is a key factor in the definition of managerial strategies. A survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 15 publications
0
34
0
Order By: Relevance
“…In contrast, the returns on implementing social standards such as SA8000 are much less clear compared with the generally high and highly visible returns on eco-efficiency (see e.g. Merli et al, 2015;Orzes et al, 2017). SA8000 implementation has been found to positively affect sales performance and labor productivity, but not firm profitability, suggesting that there is no clear economic incentive for adopting SA8000 (Orzes et al, 2017).…”
Section: (Adoption Of ) Sa8000mentioning
confidence: 98%
“…In contrast, the returns on implementing social standards such as SA8000 are much less clear compared with the generally high and highly visible returns on eco-efficiency (see e.g. Merli et al, 2015;Orzes et al, 2017). SA8000 implementation has been found to positively affect sales performance and labor productivity, but not firm profitability, suggesting that there is no clear economic incentive for adopting SA8000 (Orzes et al, 2017).…”
Section: (Adoption Of ) Sa8000mentioning
confidence: 98%
“…Management support and commitment are recognized as relevant (Santini et al, 2013), along with personal management satisfaction (Gabzdylova et al, 2009). Regarding employees, it is underlined the importance of satisfied ones (Merli et al, 2015). Lastly, the relevance of four other main drivers is pinpointed, i.e.…”
Section: Drivers To Ismentioning
confidence: 98%
“…The first explores human resources management, the improvement of the business climate, the management of workers' health and safety and the use of innovative technologies to reduce the environmental impact (Arcese et al , 2013). The second is mainly projected towards enhancing local communities' well-being, human rights defence and natural resource protection (Merli et al , 2015). Mainstream literature has demonstrated that implementing CSR strategies, both in terms of the internal and external dimensions, may be beneficial for companies (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%